Structural, Morphological, and Optical Properties and Photocatalytic Performance of Pr (3%) and Al Co-doped SrTiO3 for Dye Removal - Yuniar Sindy Mutiara Putri; Dianisa Khoirum Sandi; Fahru Nurosyid; Risa Suryana; Yofentina Iriani (Pandawa Institute, 2026)
Strontium titanate (SrTiO₃) photocatalysts co-doped with praseodymium (Pr) and aluminum (Al) were successfully synthesized using the coprecipitation method. The doping concentrations were varied with a fixed Pr content of 3 mol% and Al contents of 1, 3, and 5 mol%. The samples were characterized using X-ray diffraction (XRD), Fourier-transform infrared (FTIR), surface area analyzer (SAA), scanning electron microscopy with energy-dispersive X-ray (SEM–EDX), and UV–visible diffuse reflectance spectroscopy (UV–Vis DRS). The photocatalytic behavior of the prepared samples was evaluated by degrading methylene blue (MB) under UV C light (λ = 254 nm) exposure for 1–5 h. XRD analysis confirmed the formation of a cubic perovskite structure with the presence of Sr–O–Ti bonds identified in the FTIR spectra at about 557 cm⁻¹. Increasing the Al doping concentration resulted in larger crystallite sizes, higher crystallinity, and a reduction in the bandgap energy from 3.188 eV to 3.085 eV. SEM–EDX and SAA analyses showed an increase in particle size accompanied by a decrease in surface area. The bandgap narrowing enhanced photon absorption and improved photocatalytic activity toward the degradation of methylene blue. Overall, Pr–Al co-doping effectively modified the structural and optical properties of SrTiO₃, making it a promising material for efficient photocatalytic applications.